Implementing Human Resource Strategy in Trans Studio Garden Tanjungpinang - Satriadi; Chairunnisya, Tara; Saputra, Fery Prayoga; Apriyanti, Fhertyna; Irmawati (Ilomata International Journal of Management, 2024)
Human resources are individuals who have structured abilities from a combination of thinking skills and physical abilities in an organization. Based on the results of brief interviews with several employees, the majority of employees said they felt less confident when serving visitors, this was due to a lack of coaching or training in communicating and operating rides on an ongoing basis. The objective of this study to description implications of human resource strategies at Trans Studio Garden Tanjungpinang. The research method uses a qualitative approach. This research used the purposive sampling method obtained 5 informants. The data analyzedby using triangulation. The results of this study indicate that Trans Studio Garden Tanjungpinang, in its human resource management strategy, provides training to all employees every 3 months to increase work experience and expertise in serving visitors. The suggestions in this study that companies can carry out training, especially related to public speaking to employees, this aims to improve employee communication skills for the better.